Phosphate Homeostasis − A Vital Metabolic Equilibrium Maintained Through the INPHORS Signaling Pathway - Austin, Sisley; Mayer, Andreas (Frontiers in Microbiology, 2020)
Cells face major changes in demand for and supply of inorganic phosphate (Pi). Pi is often a limiting nutrient in the environment, particularly for plants and micro-organisms. At the same time, the need for phosphate varies, establishing conflicts of goals. Cells experience strong peaks of Pi demand, e.g. during S-phase, when DNA, a highly abundant and phosphate-rich compound, is duplicated. While cells must satisfy these Pi demands, they must safeguard themselves against an excess of Pi in the cytosol. This is necessary because Pi is a product of all nucleotide-hydrolyzing reactions. An accumulation of Pi shifts the equilibria of these reactions and reduces the free energy that they can provide to drive endergonic metabolic reactions. Thus, while Pi starvation may simply retard growth and division, an elevated cytosolic Pi concentration is potentially dangerous for cells because it might stall metabolism. Accordingly, the consequences of perturbed cellular Pi homeostasis are severe. In eukaryotes, they range from lethality in micro-organisms such as yeast (Hürlimann, 2009; Sethuraman et al., 2001), severe growth retardation and dwarfism in plants (Liu et al., 2015; Puga et al., 2014; Wild et al., 2016) to neurodegeneration or renal Fanconi syndrome in humans (Ansermet et al., 2017; Legati et al., 2015). Intracellular Pi homeostasis is thus not only a fundamental topic of cell biology but also of growing interest for medicine and agriculture